Exploring learner acceptance and experience in MOOCs among higher vocational students from a TAM perspective: a case study of college English course - Hou, Shuhua (Frontiers in Psychology, 2025)
This study investigates higher vocational students’ acceptance of a College English MOOC through the technology acceptance model (TAM). A survey of 434 students was analyzed using structural equation modeling (SEM). The findings confirm core TAM relationships: perceived ease of use (PEOU) significantly enhances perceived usefulness (PU), which in turn fosters a positive attitude toward use (ATU) and increases intention to use (IU). Furthermore, IU positively impacts the learning experience (LE). A key discovery is the negative effect of ATU on LE, suggesting that initial attitude alone does not guarantee a positive experience, which may be more critically shaped by course content and instructional design. This study enriches the TAM literature within vocational education and provides practical insights for developing MOOCs that better meet the needs of vocational learners.